AutoMoDe-Mate: Automatic off-line design of spatially-organizing behaviors for robot swarms - Mendiburu, Fernando J.; Garzón Ramos, David; Morais, Marcos R.A.; Lima, Antonio M.N.; Birattari, Mauro (Swarm and evolutionary computation, 2022)
•Automatic methods can design spatially-organizing behaviors for robot swarms.•AutoMoDe-Mate is a design method specialized in spatial organization problems.•AutoMoDe-Mate includes a module that enables robot pattern formation.•Experiments with physical robots show effectiveness in coverage and networking.•AutoMoDe-Mate outperforms baseline modular and neuro-evolutionary methods. [Display omitted] We present Mate, an automatic off-line design method specialized in the design of spatially-organizing behaviors for robot swarms. Mate belongs to the family of modular methods known as AutoMoDe. We introduce Mate to study the automatic design of collective behaviors for missions in which the swarm is subject to spatial distribution constrains. In this paper, we produce control software for three missions with specifications related to the distribution of the swarm in the environment. We conduct experiments in simulation and with a swarm of 20 e-puck robots. Alongside Mate, we also conduct experiments with two other automatic design methods: Chocolate—a state-of-the-art instance of AutoMoDe; and EvoSpace—a method based on neuro-evolution. Early studies conducted with existing modular design methods have shown their limitations in the design of spatially-organizing behaviors for robots that operate under spatial constrains. By introducing a specialized method like Mate, we expect to overcome these limitations. The aggregate results of our experiments show that Mate performs significantly better than Chocolate and EvoSpace in the missions we consider.